GRUP FACEBOOK GESAMUN SEBAGAI MEDIA BARU DALAM UPAYA MENYADARKAN MASYARAKAT AKAN PENTINGNYA IMUNISASI - Yusmawati Yusmawati (Jurnal Komunikasi, 2018)
-The presence of new media is a technological innovation that is able to change lifestyle including how to interact in society. The community turns into an information society that has a high need for information in all areas. New media, especially social media facebook become one of the most widely used media by the community to communicate. In addition to Facebook used to interact personally, many users take advantage of this social media to join or form an online community. GESAMUN or Gerakan Sadara Imunisasi is a group discussion on Facebook that was formed with the aim of creating public awareness of health especially the benefits of immunization and also as a forum for discussion of matters related to immunization. GESAMUN was born out of a sense of responsibility and concern for a variety of mixed-up news about immunization that caused many Indonesians who were still afraid and hesitant to vaccinate. The purpose of this study is to determine the role of facebook group GESAMUN in an effort to make people aware of the importance of immunization. The research methodology used is qualitative. The role of GESAMUN is to provide complete information in the form of Starter Kit, open discussion room for all members, actively provide information about the vaccine, straighten the maze and so forth.Key words : group, facebook, GESAMUN, immunization